The Efficacy of Airpower in Counterinsurgency. (15th March 2022) - Newton, Christopher; Tucker, Colin
Abstract: Since 2001, the United States has relied upon air strikes in its global counterterrorism campaign against insurgencies throughout the world. With advances in air strike technology, public opinion growing increasingly intolerant of deployments of ground forces abroad, and the proliferation of terrorist groups around the world, the use of air strikes appears to be the future of US counterterrorism policy. This study tests the efficacy of air strikes as a counterinsurgency tool by geocoordinating US air strike data and merging it with three major databases on conflict events to assess whether air strikes influence the rate of insurgent attacks. Our analysis reveals that air strikes reduce insurgents' capacity to carry out attacks over the long term. At the same time, air strikes carry a short-term, provocative effect on insurgent attacks when they result in civilian fatalities. Finally, there is some evidence that air strikes increase attack attempts, but these attempts are not always successful, nor directed toward government forces.